High Calcium and Vitamin D Fortified in Enhancing Postmenapausal Bone Turnover - Arifin, Zainal (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To compare the effect of consuming vitamin D fortified high calcium milk (HCM) with placebo milk supplementationâs effect to bone formation and resorptionâs marker to post-menopausal women in Jakarta, Indonesia, in four months duration. Methods: This is a double blind randomized control trial to know the effect of high calcium (1200 mg/day) milk consumption compared to low calcium milk consumption to the change of bone turnoverâs chemical marker in post-menopausal women in Indonesia. Participants are women aged more than 55 years, which are patients of Yasmin Menopause and Osteoporosis Clinic, RSCM. Subject of study is classified into two groups, the first group was given two portion (60 g) of high calcium milk (HCM), and other group as control was given two portion (60 g) of low calcium milk, each day for 16 weeks. A comparison between the level of bone markers (CTelopeptide (CTX), Peptide Procollagen-I (P1NP), Osteocalcin (OC)) in week 0, 2, 8 and 16 was done. Post intervention, the result was statistically calculated with ANOVA and the mean result comparison to subject was analyzed with Tukey-Kramer test. Results: There are no significant differences between two groups on age, Body Mass Index (BMI), Bone Mineral Density (BMD) and calcium intake characteristics. There is CTX (CTelopeptide) reduce to 34% in two weeks of supplementation to HCM group cohort. OC (Osteocalcin) was also reduced in 16 weeks supplementation to subject group, reduced to 10% on week 2, 18% on week 8, and 32% on week 16. Peptide Procollagen-I (P1NP) was reduced to 15% on week 8, and 28% on week 16 in subject group. High calcium and vitamin D fortified milk that was used, is proven could improve vitamin D state, reduce PTH level and reduce bone turnover significantly. Conclusion: High calcium and vitamin D fortified milk supplementation gives better result compared to low calcium milk supplementation in reducing bone turnover in post-menopausal women. [Indones J Obstet Gynecol 2010; 34-1:31-8] Keywords: post-menopausal women, high calcium and vitamin D fortified milk, C-Telopeptide, Peptide Procollagen-I, Osteocalcin, vitamin D state